DNA damage-induced heterogeneous nuclear ribonucleoprotein K sumoylation regulates p53 transcriptional activation. - Pelisch, Federico Gaston (2012)
Heterogeneous nuclear ribonucleoprotein (hnRNP) K is a nucleocytoplasmic shuttling protein that is a key player in the p53-triggered DNA damage response, acting as a cofactor for p53 in response to DNA damage. hnRNP K is a substrate of the ubiquitin E3 ligase MDM2 and, upon DNA damage, is de-ubiquitylated. In sharp contrast with the role and consequences of the other post-translational modifications, nothing is known about the role of SUMO conjugation to hnRNP K in p53 transcriptional co-activation. In the present work, we show that hnRNP K is modified by SUMO in lysine 422 within its KH3 domain, and sumoylation is regulated by the E3 ligase Pc2/CBX4. Most interestingly, DNA damage stimulates hnRNP K sumoylation through Pc2 E3 activity, and this modification is required for p53 transcriptional activation. Abrogation of hnRNP K sumoylation leads to an aberrant regulation of the p53 target gene p21. Our findings link the DNA damage-induced Pc2 activation to the p53 transcriptional co-activation through hnRNP K sumoylation.